139k views
1 vote
-3 (2x + 1)/4 = 3 (x + 4) + 3/4

-3 (2x + 1)/4 = 3 (x + 4) + 3/4-example-1
User Jeff Tang
by
5.2k points

2 Answers

4 votes

Answer: x=-3


(-3(3x+1))/(4) = 3(x+4) +3/4\\(-3x-3)/(4) = 3x+12+3/4\\(-3x-3)/(4)=3x+15/4\\4*(-3x-3)/(4)= 3x+15/4\\ *4\\-3x-3= 3x+15\\+3 +3\\-3x=3x+18\\-3x -3x\\-6x=18\\/-6 -/6 \\x= -3 \\\\

I think i did this right for you, hopefully this helped

User Tarji
by
5.2k points
3 votes

Answer:


x = -3

Explanation:


\frac{-3(2x + 1)}4 = 3(x + 4) + \frac34 \text{ // Distribute}\\\\\frac{-6x - 3}4 = 3x + 12 + \frac34 \text{ // Multiply by 4}\\\\-6x - 3 = 12x + 48 + 3\\-6x - 3 = 12x + 51 \text{ // Add 6x and subtract 51}\\-54 = 18x \text{ // Divide by 18}\\-3 = x

User CalleKhan
by
5.4k points